2019
DOI: 10.1021/jacs.9b10507
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Electrochemical Applications of Chiral Imprinted Mesoporous Ni Surfaces

Abstract: The enantioselective synthesis of chiral compounds is of crucial importance for a wide range of potential applications, especially in cosmetic and pharmaceutical industries. Recently, chiral imprinted mesoporous platinum films, produced by the electrodeposition of the metal, in the simultaneous presence of a lyotropic liquid crystalline phase of non-ionic surfactants as mesoporogens and chiral templates, have been applied as electrocatalysts and selective stationary phases for the asymmetric synthesis and sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 107 publications
1
32
0
1
Order By: Relevance
“…Changing the pulse time greatly influences the overall enantioselectivity and ee values of over 90 % could be obtained under optimized conditions. Very recently, similar results have also been obtained with electrodes made out of imprinted mesoporous nickel, despite the fact that it is a non‐noble metal, which is less stable from a chemical and mechanical point of view …”
Section: Properties and Applicationssupporting
confidence: 67%
See 1 more Smart Citation
“…Changing the pulse time greatly influences the overall enantioselectivity and ee values of over 90 % could be obtained under optimized conditions. Very recently, similar results have also been obtained with electrodes made out of imprinted mesoporous nickel, despite the fact that it is a non‐noble metal, which is less stable from a chemical and mechanical point of view …”
Section: Properties and Applicationssupporting
confidence: 67%
“…Very recently,s imilar resultshave also been obtained with electrodes made out of imprinted mesoporous nickel, despite the fact that it is an on-noblem etal, which is less stable from a chemicaland mechanical point of view. [36] Other electrochemical applications of chirally encoded metal surfaces Another important aspect in the frame of chiral technologies is related to chiral separation because it can be used for many aspectss uch as controlling enantiopure production, checking racemization, and for pharmacokinetics tudies. Apart from conventional chiral separation methods like HPLC, electroseparation techniques also have an important application potential because they allow for increasing the separation efficiency of chiral molecules by an easy fine-tuning of the interaction between chiral compounds and the stationaryp hase.…”
Section: Chiral Recognition At Metal and Metal Oxides Surfacesmentioning
confidence: 99%
“…Reproduced with permission. [ 155 ] Copyright 2019, American Chemical Society. C) a) Fabrication of photothermal colloid antibodies (PCAs) and b) experimental setup of the action of PCAs.…”
Section: Green Strategies For Benign Mipsmentioning
confidence: 99%
“…produced chiral mesoporous Ni surfaces by electrodeposition of Ni in the presence of a nonionic surfactant (Brij C10) and a chiral compound (phenylethanol, PE) (Figure 6B). [ 155 ] The physical and electrochemical characteristics of the imprinted Ni film demonstrated that it could be applied in the enantioselective electroreduction of a prochiral compound, acetophenone, resulting in the preferential generation of one or the other PE enantiomer. From a sustainability point of view, compared with mesoporous Pt surfaces, [ 170 ] the imprinted mesoporous Ni surfaces were less costly and had fewer adverse effects.…”
Section: Green Strategies For Benign Mipsmentioning
confidence: 99%
“…Concerning the latter aspect, CIMMs have been employed as working electrodes, yielding initially an only moderate enantiomeric excess (%ee) [14a] . However, by fine‐tuning the conditions of the electroreduction, a very high %ee (>95%) could be achieved, especially when using a pulsed electrosynthesis strategy with imprinted bimetallic Pt−Ir alloys as electrode material [14b–d] …”
Section: Introductionmentioning
confidence: 99%